Quality of life and interdisciplinarity: the necessity of home care programs in the prevention of complications in old people with dysphagia - Salzani Mendes, Fernanda; Aintablian Tchakmakian, Lucy (O Mundo da Saúde, 2009)
Changes of the age and demographic profiles of the population evidence alterations in the aging process regarding nutritional and phonoaudiologic condition. Old people with dysphagia become more fragile and may present complications such as aspiratory pneumonia and alterations in food ingestion that may compromise their health. A health assistance alternative is home care services that use technical support of an interdisciplinary team to take care in a global way of individuals having difficulties to arrive at ambulatory services. This work aims to show the importance of early diagnosis and intervention in old people with dysphagia, in an attempt to improve nutritional condition and quality of life, thus diminishing health complications for a group participant of a Home Care Program in São Paulo City. On the basis of a of quantitative-qualitative field study using an analytical descriptive method, we observed that early intervention of the care team produced some improvement in the nutritional and phonoaudiologic profiles of subjects in the sample, but not a statistically significant association between variables “consistencies of foods” and “modifications from pre- and post-intervention nutritional diagnosis (p > 0,10).